Reducing response burden in the American Community Survey : proceedings of a workshop - Plewes, Thomas J. (National Academies Press, 2016)
In recent years, the American Community Survey (ACS) - a mandatory household survey that replaced the supplementary "long form" of the census - has seen an increase in nonresponse and criticism for invasion of privacy and excessive burden. As part of the U.S. Census Bureau's continual efforts to improve the Survey, this workshop was called to investigate response burden, focusing on four main topics: matrix sampling to reduce the number of individuals that various questions are posed to; direct substitution of information from administrative records, eliminating some questions; having a separate, reduced-size questionnaire that eliminates unreasonable questions for respondents living in group quarters; and a communication and education strategy to increase cooperation with the request to participate